Creating successful and unique schools: leadership, context and systems thinking perspectives. Issue 1 (18th August 2020) - Gurr, David; Longmuir, Fiona; Reed, Christopher
Abstract : Purpose: Through discussion of research about the leadership of two schools, this paper explores the complexity of school leadership and how various contextual elements interact with the work of principals in schools that are attempting to create inclusive, rich, worthwhile and unique schools. A systems thinking leadership and context model is developed to frame the exploration of the two cases, which, in turn, helps inform the veracity and development of the model. Design/methodology/approach: The research reported is broadly based on multiple-perspective case studies that have included individual and/or group interviews with school leaders, teachers, students, parents and/or school council members, observation and document analysis. The focus for this paper is on evidence from the cases that elucidate the model. Findings: A leadership and context view of schools helps to understand how school leaders work with, within and influence various contextual factors to develop schools that are both successful and unique. The cases demonstrated how individual leadership factors including career histories, personalities and values coalesced with school and broader community factors in reciprocal ways that resulted in school-specific improvements. Research limitations/implications: The research is limited by the nature of bounded, small number, qualitative case research. Nevertheless, the authors suggest that the school leadership and context systems model the authors presented captures much of the complexity of the successful leadership of these schools. The authors further suggest that this model provides a conceptual contribution to the study of successful school leadership that moves beyond more linear leadership views. Implications of this research and the conceptual contributions that the authors advance are that leadership and context should be considered in reciprocal and nuanced ways across a complex variety of contextual levels. Practical implications: These cases explore the growth and development of new school communities and capture the dynamic interactions between leadership and context within the complex arrangements of policy, system, history and community. The cases demonstrated how individual leadership factors, including career histories, personalities and values, coalesced with school and broader community factors in reciprocal ways that resulted in school-specific improvements. These findings and the system thinking leadership model help school leaders to consider their own work in developing successful and unique schools. Social implications: School leadership is important for school success, and schools that meet student and community needs are important for society. The authors' system thinking leadership model helps school leaders improve their practice in creating more interesting and successful schools that meet student and community needs. Originality/value: At a time when international sharing of information and international testing of schools is pushing towards a uniformity of thinking about what good schools should be, the reality of leading schools is far different. This paper contributes to the knowledge about how school leaders navigate contextual complexities to create successful and unique schools that meet local needs.